Imeum Mukim Advocacy in Prevention of Environmental Pollution in Aceh Jaya According to Customary and Islamic Law - Syahbandir, Mahdi; MAZ, Dahlawi; Alqarni, Wais; Samad, Munawwarah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This study aims to discuss the advocacy of imeum mukim in preventing environmental pollution in Aceh Jaya according to customary and Islamic law. The research is an empirical legal study, while the research approach is a case study approach, which is a study that analyzes a particular case. The theory used is the role and authority theory associated with customary and Islamic law. This study concludes that imeum mukim has a vital role and authority in Acehnese society because imuem mukim can resolve cases at the mukim level if it is unresolved at the village level. Then Imeum Mukim in Aceh Jaya has been advocating and socializing the prevention of environmental pollution by revitalizing customary rules, making qanuns at the mukim and village levels that accommodate the protection of the environment, for example, maintaining watersheds and prohibiting logging, including protecting certain animals. In addition, Imuem Mukim can also encourage CSR funds from companies to assist orphans, the poor, and environmental conservation. Furthermore, environmental pollution in the perspective of customary law is accommodated in customary rules and prohibitions. This is because customary law has philosophical, juridical, and sociological powers that have become living law. Meanwhile, in the perspective of the Islamic law that polluting the environment is a prohibition that brings God's wrath, it also destroys environmental sustainability and human benefit in general. On the other hand, preserving the environment is an obligation humans must carry out.